Analisa Kerjasama Australia- India Dalam Penjualan Uranium - Ali Martin; Rodiyatun Rodiyatun (LP2M, 2019)
Abstract Establishment of an agreement between Australia and India to sell uranium to India. India is one of the countries in Asia that has a very rapid rate of economic growth. In this study the author will explain about Australia's interest in selling uranium to India and its factors. Which will change the geopolitical dynamics and strategies of several countries, but the decision is related to changes in the balance of power in Asia and the central role of the United States in Australian security policy.